Photocatalytic removal of antibiotics by MOF-derived Ti3+- and oxygen vacancy-doped anatase/rutile TiO2 distributed in a carbon matrix - Chen, Xiangyan; Peng, Xin; Jiang, Longbo; Yuan, Xingzhong; Fei, Jia; Zhang, Wei (Chemical engineering journal (Lausanne, Switzerland : 1996), 2022)
[Display omitted] •Ti3+- and Ov-doped A/R-TiO2 with a carbon matrix was prepared by calcining Ti-MOF.•The existence of Ti3+ and Ov in TiO2 leads to a new energy band between VB and CB.•The charge separation was enhanced by the heterojunction structure of A/R-TiO2.•Derivatives of Ti-MOF enhanced the rate of antibiotic photodegradation. Residual antibiotic in ecosystems are an environmental problem that urgently needs to be solved. Developing efficient and green photocatalysts is an attractive option for the removal of antibiotics. In this work, a titanium metal organic framework (Ti-MOF) was calcined in an air atmosphere to obtain Ti3+- and oxygen vacancy (Ov)-doped anatase and rutile heterojunction TiO2 (A/R-TiO2) distributed in a carbon matrix. Through XPS, UV–Vis, ESR and other characterizations, it is proven that Ti3+ and Ov exist in heterojunction TiO2. And the characterization results that Ti3+- and Ov-doped A/R-TiO2 exhibits expanded visible light absorption and enhanced separation of charge carries. The photocatalytic degradation efficiency of tetracycline (TC) by the optimal Ti-MOF derived materials reaches 87.03% and the degradation rate of chlortetracycline (CTC) reaches 78.91% in 60 min. When studying the effect of water matrix on the removal of TC, it was found river water has the highest removal rate of TC (70.76%), followed by tap water (66.37%), lake water (61.19%), and hospital wastewater (52.68%). This shows that the carbon coated Ti3+- and Ov-doped A/R-TiO2 is effective for the degradation of antibiotics. In addition, the carbon coating formed by the pyrolysis of the Ti-MOF as a barrier layer can prevent the oxidation of Ti3+ and Ov, which make the prepared materials have good stability and repeatability. In this work, hole (h+) and superoxide radical (•O2−) are the active substances that play a major role in the degradation system, while the effect of hydroxyl radicals (•OH) is small. Finally, a possible mechanism of carbon coated Ti3+- and Ov-doped TiO2 for photocatalytic degradation is proposed.